Ethnicity, Identity, and the Development of Nationalism in Iran - Yaghoubian, David N. (David Nejde), 1967- (Book collections on Project MUSE., 2014)
Ethnicity, Identity, and the Development of Nationalism in Iran investigates the ways in which Armenian minorities in Iran encountered Iranian nationalism and participated in its development over the course of the twentieth century. Based primarily on oral interviews, archival documents, personal memoirs, memorabilia, and photographs, the book examines the lives of a group of Armenian-Iranians--a truck driver, an army officer, a parliamentary representative, a civil servant, and a scout leader--and explores the personal conflicts and paradoxes attendant upon their layered allegiances and compound identities. In documenting individual experiences in Iranian industry, military, government, education, and community organization, the five social biographies detail the various roles of elites and nonelites in the development of Iranian nationalism and reveal the multiple forces that shape the processes of identity formation. Yaghoubian combines these portraits with theories of nationalism and national identity to answer recurring pivotal questions about how nationalism evolves, why it is appealing, what broad forces and daily activities shape and sustain it, and the role of ethnicity in its development.